A global response to elder abuse and neglect : building primary health care capacity to deal with the problem worldwide : main report. (World Health Organization, 2008)
Of report from ChileFocus groups; Summary of report from Costa Rica; Focus groups; Workshops; Summary of report from Kenya; Focus groups; Workshops; Summary of report from Singapore; Focus groups; Workshops; Summary of report from Spain; Focus groups; Workshops; Workshop with PHC professionals and social workers; Summary of report from Switzerland; Focus group discussions; Workshops.